Coping with Mom's breast cancer: impact of parental cancer on African-American adolescents - Dockery, Kimberley D. (Kansas State University, 2008)
Parental breast cancer is an illness that affects the patient as well as the entire family. A review of literature shows that very limited research exists in the area of parental breast cancer. Research is needed on interactive effects of the patient and family, especially in understanding the experience of African-American families. This report explores theory and family literature to address how clients can be served when facing parental breast cancer. Further research is needed to examine the clinical implications for the clients by enhancing more coping strategies for adolescents and their families who are coping with the diagnosis and treatment of the mom's breast cancer.
Keywords: Parental Breast Cancer; Adolescents; African-Americans; Sociology, Individual and Family Studies (0628)